The knowledge attitude and practice (KAP) of mothers of asthmatic children toward asthma in Khartoum asthma clinics - Noureddin, Ahmed Abdulgadir (Sci Rep, 2019)
Prevention of asthma attacks is one of the major challenges of public health. Sufficient knowledge and positive attitudes and correct practices are crucial for the prevention of exacerbations. However, there is insufficiency of information in regard to these in Sudan. The aim of this study was to assess the knowledge and to identify the attitude and practice of mothers of asthmatic children concerning their use of inhalers, compliance to preventers and to measure its effect on the severity of the disease in their children. A sample of 100 consecutive mothers of asthmatic children was enrolled. Any mother with a child diagnosed with bronchial asthma for more than 3 months, and who attended the outpatient clinic of paediatric asthma in Soba or Ahmed Gasim hospitals or the Emergency room of Ahmed Gasim or Ibrahim Malik hospital in the period from 1st to 31st of October 2016 was eligible to be included. Asthma was believed to be infectious by 7% of the respondents. 17% of the mothers thought asthma was preventable by a vaccine. 21% found inhaler use unacceptable. Half of the mothers (50%) did not use the inhaler correctly. Most of the mothers (69%) did not use the inhaler if symptoms were mild and 53% didn’t use preventers. The severity of asthma was found to be significantly associated with the attitude and practice of mothers (P < 0.05). In conclusion, sustained efforts are required to increase knowledge about all dimensions of asthma and its management among patients and to disperse myths and misguided judgments regarding the disease and its treatment.